ETHNOMATHEMATICS MODULE BASED ON RME (REALISTIC MATHEMATICS EDUCATION) ON STUDENTS' NUMERATION AND CRITICAL REASONING - Linda Dwi Saputri; Kasihani Lestari; Vera Riyanti (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Numeracy skills are among those that need to be developed in the 21st century, so they are often a topic in educational research. Furthermore, the character of critical reasoning is a frequently discussed topic because it is part of the Pancasila student profile dimension. However, based on the results of the 2024 education report card in Melawi Regency, numeracy skills and critical reasoning character are still low. Therefore, efforts are needed to improve students' numeracy skills and critical reasoning character through the use of RME (Realistic Mathematics Education)-based ethnomathematics modules. The purpose of this study was to determine the effectiveness of the RME-based ethnomathematics module of the Dayak Muntak tribe in improving students' numeracy skills and critical reasoning character. This research used an experimental design with a pretest-posttest control group. The subjects of this study were 56 students from the control class and 57 from the experimental class. This research instrument used numeracy test questions and a critical reasoning character questionnaire. The results of the study indicate that implementing the RME-based ethnomathematics module had a significant and effective impact on students' numeracy and critical reasoning skills. This is evident from the results of the Mann-Whitney U-test, which demonstrated a treatment effect, and the N-Gain test, which indicated the level of improvement in numeracy and critical reasoning skills.Kemampuan numerasi merupakan satu diantara kemampuan yang perlu dikambangkan pada abad XXI, sehingga sering menjadi topik dalam penelitian pendidikan. Selain itu, topik yang sering dibahas adalah karakter bernalar kritis karena merupakan bagian dari dimensi profil pelajar Pancasila. Namun, berdasarkan hasil rapor pendidikan tahun 2024 di Kabupaten Melawi kemampuan numerasi dan karakter bernalar kiritis masih rendah. Oleh karena itu, perlu upaya untuk meningkatkan kemampuan numerasi dan karakter bernalar kritis siswa melalui penggunaan modul etnomatematika berbasis RME (Realistic Mathematics Education). Tujuan penelitian ini adalah mengetahui efektivitasÂ modul etnomatematika suku Dayak Muntak berbasis RME untuk meningkatkan kemampuan numerasi dan karakter bernalar kritis siswa. Metode penelitian ini menggunakan metode eksperimen dengan desain pretest-posttest control group. Subjek penelitian ini terdiri dari 56 siswa dari kelas kontrol dan 57 siswa dari kelas eksperimen. Instrumen penelitian ini menggunakan soal tes numerasi dan angket karakter bernalar kritis. Hasil penelitian menunjukkan bahwa penerapan modul etnomatematika berbasis RME memberikan pengaruh yang signifikan serta efektif dalam meningkatkan kemampuan numerasi dan karakter bernalar kritis peserta didik. Hal tersebut terlihat dari hasil uji U-Mann Whitney yang menunjukkan adanya pengaruh perlakuan, serta uji N-Gain yang mengindikasikan tingkat efektivitas peningkatan kemampuan numerasi dan karakter bernalar kritis.Â